2009
DOI: 10.1016/j.jfoodeng.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of coumarin-enriched Japanese green teas and their particular flavor using electronic nose

Abstract: a b s t r a c tConventionally, tea flavor is analyzed through the use of a combination of gas chromatography-mass spectrometry and human taste panel. These methods present time-consuming or inaccurate factor. In this work, a rapid, accurate and nondestructive approach was put forward to identify coumarin-enriched Japanese green teas and evaluate their particular flavor using electronic nose (E-nose) technique. The multivariable analyses including principal component analysis and cluster analysis were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Its authors prove that the approaches using traditional sample handling procedures do not give adequate results in that case. Similar conclusions have been made by the authors of [54] and [55] dealing with identification of teas and analysis of human expired air: application of a gas trap and preconcentration using adsorbents to remove water vapor made it possible to improve analysis efficiency in the both cases.…”
Section: Sample Enrichment Methodssupporting
confidence: 69%
“…Its authors prove that the approaches using traditional sample handling procedures do not give adequate results in that case. Similar conclusions have been made by the authors of [54] and [55] dealing with identification of teas and analysis of human expired air: application of a gas trap and preconcentration using adsorbents to remove water vapor made it possible to improve analysis efficiency in the both cases.…”
Section: Sample Enrichment Methodssupporting
confidence: 69%
“…It was demonstrated that the e-nose successfully characterized the drying temperature-dependent trend of coumarin content during the manufacturing process, and could be employed to identify green teas with particular flavor and evaluate the tea flavor. [25] A novel electronic nose based on miniaturized surface acoustic wave (SAW) sensor arrays coupled with solid phase micro extraction process(SPME) enhanced headspace-analysis was studied by Bari´e et al [26] . With the SPME technique this system was used for rapid determination of the volatile organic compounds for food quality monitoring.…”
Section: Biomimetic Systemsmentioning
confidence: 99%
“…The total antioxidant capacity was determined coulometrically with electrogenerated bromine in accordance with [28,29]. The amount of antioxidant was expressed by the charge required for generation of equivalent quantity of bromine, coulombs per 100 mL of undiluted sample.…”
Section: Tea Brands Discriminationmentioning
confidence: 99%